Effects of aligned fractures on the response of velocity and attenuation ratios to water saturation variation: a laboratory study using synthetic sandstones. (23rd May 2016) - Amalokwu, Kelvin; Best, Angus I.; Chapman, Mark
ABSTRACT: P‐wave‐to‐S‐wave ratios are important seismic characterization attributes. Velocity ratios are sensitive to the petrophysical properties of rocks and to the presence of gas. Attenuation ratios have also been shown to be sensitive to the presence of partial liquid/gas saturation. The relationship between liquid/gas saturation and P‐wave and S‐wave ratios has been used to distinguish gas‐saturated rocks from liquid‐saturated rocks. Aligned fractures are common in the Earth's crust and cause seismic anisotropy and shear wave splitting. However, most existing relationships between partial gas/liquid saturation and P‐wave and S‐wave ratios are for non‐fractured rocks. We present experimental results comparing the effects of changing water saturation on Q s / Q p versus V p / V s ratios between a non‐fractured rock and one containing fractures aligned parallel to wave propagation direction. We also study the effects of aligned fractures on the response of V p / V s to changing water saturation using synthetic fractured sandstones with fractures aligned at 45 o and parallel to the wave propagation direction. The results suggest that aligned fractures could have significant effects on the observed trends, some of which may not be obvious. Fractures aligned parallel to wave propagation could change the response of Q s / Q p versus V p / V s ratios to water saturation from previously reported trends. Shear wave splitting due to the presence of aligned fractures results in two velocity ratios ( V p / V s1 and V p / V s2 ). The fluid independence of shear wave splitting for fractures aligned parallel to wave propagation direction means the difference between V p / V s1 and V p / V s2 is independent of water saturation. For fractures aligned at oblique angles, shear wave splitting can be sensitive to water saturation and consequently be frequency dependent, which can lead to fluid and frequency‐dependent differences between V p / V s1 and V p / V s2 . The effect of aligned fractures on V p / V s ratios not only depends on the fracture effects on both P‐wave and S‐wave velocities but also on the effects of water saturation distribution on the rock and fracture stiffness, and hence on the P‐wave and S‐wave velocities. As such, these effects can be frequency dependent due to wave‐induced fluid flow. A simple modelling study combining a frequency‐dependent fractured rock model, and a frequency‐dependent partial saturation model was used to gain valuable interpretations of our experimental observations and possible implications, which would be useful for field seismic data interpretation.